EVALUATION OF “SOLID WATER” PLASTIC AS A CALIBRATION PHANTOM FOR ELECTRON BEAM DOSIMETRY - KAKANAPORN, Chumpot; THAMWINITCHAI, Porntip; ROJPONGKASEM, Somporn (The ASEAN Journal of Radiology, 2023)
In radiation dosimetry protocols, plastic is allowed as a phantom material for electron beams calibration. The water equivalency of the solid phantom should be investigated. This study evaluated a commercially available photon-electron Solid Water phantom as phantom material in terms of output calibration, depth ionization measurements and beam energy characterization by comparing with measurement in water. Measurements were performed for 8, 10, 12 and 15 MeV electron beams with field sizes of 10 x 10 cm? and 14 x 14 cm*. The dosimetry system is a Farmer 0.6 cc graphite walled ion chamber. Ionization measurements were taken at various depths and the depths to the selected percent depth ionization line (R, R, and R,) match to within 2 mm. of those measured in water, which would result in calculated incident energies within + 0.4 MeV. Evaluations compared with absorbed doses calculated from ionization measurements using IAEA calibration protocol resulted in a discrepancy in calculated peak dose rate. Eliminating this discrepancy requires an ionization ratio correction (h,). The variations lead to the suggestion that any phantom material need acceptance testing SEP. - DEC. 1999. Volume V Number II] before clinical use.